Cervical Cancer Prevention: The Role of the Nurse and Medical Care in Primary and Secondary Cancer Prevention - Katarzyna Plagens-Rotman; Piotr Merks; Magdalena Pisarska-Krawczyk; Katrzyna Bojanowska; Ewa Jaguszewska; Anna Lewek; Klaudyna Madziar; Karina Kapczuk; Tomasz Goździewicz; Milena Guszczyńska-Losy; Magdalena Durda-Masny; Dawid Luwański; et al. (IMR Press, 2023)
Objective: Although these days the priority is to fight the Covid-19 pandemic, the importance of human papillomavirus (HPV) infection is not to be neglected. Mechanism: Cervical cancer is caused mainly by a chronic infection with one or more of the high-risk subtypes of HPV -most commonly a sexually transmitted disease acquired early in life. Most HPV infections go away on their own, but some can lead to a precancerous state that, if left untreated, can undergo complete neoplastic transformation. Findings in Brief: There is a hope that in the future the combination of screening tests with vaccinations against oncogenic strains of HPV will allow reductions in the percentage of those contracting cervical cancer. Conclusions: The importance of educational activities should be emphasized in developmental gynecology in the context of oncological prevention. The roles of both doctors and nurses are important here. During the Covid-19 Pandemic, these kinds of activities are not to be abandoned. In addition, efforts should be made to develop more practical and workable HPV and cervical screening strategies for use during a pandemic.